PERILAKU KECURANGAN AKADEMIK MAHASISWA DALAM PROSES PERKULIAHAN - Amjad Salong (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2018)
The purpose of this study was to determine how the image of academic cheating behavior of students in the lecture Student Accounting Concentration of Forces in 2014 and 2015 FKIP Economics. This study uses primary data. The primary data through questionnaires distributed directly to students accounting concentration of forces in 2014 and 2015. Data collection techniques in this study was a questionnaire. The number of samples in this study were 48 students of Economic Studies Program Accounting Concentration Forces in 2014 and 2015. These results indicate that the behavior of academic cheating is at a medium level which students still do a lot of good academic cheating in the exam as well as the provision of duty until in the lecture.